Wealth over health: Superior, Arizona and the Magma mine 1910-1982 - Doucette, Hailey Rae, author; Childers, Michael, advisor; Orsi, Jared, committee member; Martinez, Doreen, committee member (Colorado State University. Libraries, 2023)
The Magma mine in Superior, Arizona quickly became one of Arizona's most productive underground copper mines in the twentieth century. But the wealth of the company came at the cost of the lives of workers, not only through death but also illness, injury, and in its later years, unfair pay. This thesis traces the history of the Magma mine and its environmental history. As the mine rapidly expanded, it cost miners their livelihood. Chapter one looks at the growth of Superior alongside the Magma mine starting in the 1920s. Chapter two analyzes the events that led to the Magma mine's unionization in 1957 and the strikes that followed. Lastly, chapter three examines the events that led to the closure of the Magma mine in 1982.